IMPLEMENTASI PENDISTRIBUSIAN ZAKAT FITRAH DI DESA KUTA TINGGI ACEH - Khairuddin khairuddin (JURIS (Jurnal Ilmiah Syariah), 2020)
Zakat Fitrah is issued during the month of Ramadan. Every Muslim must release 2.8 kg of rice, both children and adults. The purpose of giving zakat is to clean the soul of muzakki, in addition, to ease the burden on the poor so as to cause compassion among humans. Through this research can find out how the implementation of the distribution of Zakat Fitrah in Kuta Tinggi village and how the Islamic legal review of the distribution of Zakat Fitrah in Kuta Tinggi Village. This study uses qualitative descriptive. The results of the study obtained the distribution of Zakat Fitrah in Kuta Tinggi village one day before the feast day and given to four asnaf, namely the general public, amil, Islamic boarding school children and mosques. Reviewing Islamic law, giving alms to all people and mosques does not have a foundation because those who are entitled to get Zakat Fitrah have been determined by Allah in al-Qur'Aan surah Al-Taubah verse 60.